Antibacterial Thin Film Composite Polyamide Membranes Prepared by Sequential Interfacial Polymerization. Issue 7 (18th June 2020) - Zhai, Xiaofei; Ye, Jianlong; He, Yaoting; Ahmatjan, Zulpiyam; Zhang, Yufeng; Lin, Song; Wang, Chunhao; Hu, Xiaoyu; Meng, Jianqiang
Abstract: In this work, thin film composite polyamide (PA) membranes are modified by polyethyleneimine (PEI) and 2, 6‐diaminopyridine (DAP) through sequential interfacial polymerization to fabricate contact active antibacterial membranes. The modified membranes show improved hydrophilicity and enhancement of zeta potential. Upon tethering with PEI and DAP onto the PA membranes, the membrane flux increases from 35.7 to 46.7 and 50.0 L m −2 h −1, respectively. Further the salt rejection rate improves from 96.6% to 98.0% and 98.8%, respectively. The PA‐PEI membranes have a better antibacterial performance than PA‐DAP, with a bacteria killing ratio for both Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) over 96.7%, while a commercial LC LE‐4040 membrane presents bacteria killing ratio of 13.3% for E. coli and 8.4% for S. aureus, respectively. Abstract : Contact active antibacterial reverse osmosis membranes are fabricated through sequential interfacial polymerization. Polyethyleneimine and 2, 6‐diaminopyridine react with residue acyl chloride groups on the underlying polyamide layer and form topmost functional layers. The polyethyleneimine modified membranes show the better antibacterial property with a bacteria killing ratio of over 96.7% for both Escherichia coli and Staphylococcus aureus than diaminopyridine modified membranes.